Mitsein, tecnica e linguaggio. Il fondamento ecologico dell’umano - De Stefano, Lorenzo (Bollettino Filosofico, 2023)
The aim of the essay is contextualizing Heidegger’s views on technology and language in the light of contemporary anthropological theories of Tomasello and Malafouris. Starting from the well-known dichotomy between man and animal in relation to the world, as exposed in the 1929-30 work The Fundamental Concepts of Metaphysics, we will discuss Heidegger onto-anthropological framework in relation with Tomasello’s category of intentionality. In this context, we test if Heidegger’s discontinuity between man and animal is still actual and analyze how the concept of Mitsein could still be considered an essential category for anthropology. An ecological theory will emerge about the origin of language and technology, considered beyond the subject-object scheme of western metaphysics. Keywords: Anthropology, Heidegger, Language, Mitsein, Technology